Body composition parameters and functional status test in predicting future acute exacerbation risk among hospitalized patients with chronic obstructive pulmonary disease. Issue 11 (November 2021) - Karanikas, Ioannis; Karayiannis, Dimitrios; Karachaliou, Alexandra; Papanikolaou, Aggeliki; Chourdakis, Michail; Kakavas, Sotirios
Summary: Background & aims: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Nutritional and functional status derangement is a commonly seen in COPD patients, and this is associated with a higher disease severity and mortality. To assess body composition analysis - measured by segmental multi-frequency bioelectrical impedance analysis (BIA)- and functional status and investigate their relationship with the COPD acute exacerbation risk. Methods: Eighty COPD patients admitted to hospital for COPD acute exacerbation were prospectively followed-up for one year after discharge, focusing on a new incidence of COPD acute exacerbation. Following discharge, participants' body composition was assessed with the use of segmental multi-frequency BIA, whereas physical function by performing 5-repetitions and 30 s sit-to-stand (STS) tests. Unadjusted and multivariate logistic regression analyses were performed to evaluate the ability of the various measures to predict incidence of future COPD acute exacerbation in one-year period. Results: Seventy-six out of 80 participants completed the study and were analyzed. Fifty-one [24 male (47.1%)] out of 76 participants (67.1%), mean aged of 69.3 ± 8.9 years, developed at least one new COPD acute exacerbation during the one year follow-up. The probability of COPD acute exacerbation in one year was significantly related to BMI (OR = 0.75, 95% CI; 0.61–0.91, p = 0.004) and Fat Free Mass (OR = 0.88, 95% CI; 0.79–0.97, p = 0.012) after adjustment for sex, age and smoking index (pack × years). Both 5-repetitions and 30 s STS tests had a good predictive ability for the incidence of COPD acute exacerbation in one year (AUC = 0.80, 95% CI; 0.65–0.95, p = 0.009 and AUC = 0.83, 95% CI; 0.70–0.96, p = 0.004, respectively). Conclusion: In an observational study among patients admitted with COPD acute exacerbation, body composition analysis parameters and functional status are related to acute exacerbation risk incidence.